Nucleic Acid-Based Technologies Targeting Coronaviruses. Issue 5 (May 2021) - Le, Thi Khanh; Paris, Clément; Khan, Khadija Shahed; Robson, Fran; Ng, Wai-Lung; Rocchi, Palma
Abstract : The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is currently creating a global health emergency. This crisis is driving a worldwide effort to develop effective vaccines, prophylactics, and therapeutics. Nucleic acid (NA)-based treatments hold great potential to combat outbreaks of coronaviruses (CoVs) due to their rapid development, high target specificity, and the capacity to increase druggability. Here, we review key anti-CoV NA-based technologies, including antisense oligonucleotides (ASOs), siRNAs, RNA-targeting clustered regularly interspaced short palindromic repeats-CRISPR-associated protein (CRISPR-Cas), and mRNA vaccines, and discuss improved delivery methods and combination therapies with other antiviral drugs. Highlights: Nucleic-acid based therapies are worth developing against coronavirus (CoV) outbreaks because of their high specificity and rapid development. Several key therapeutic nucleic acid (TNA) strategies, including antisense oligonucleotides (ASOs), siRNA, and RNA-targeting clustered regularly interspaced short palindromic repeats-CRISPR-associated protein (CRISPR-Cas) technologies targeting the viral genome are potentially applicable to combat CoVs. mRNA vaccines are attractive candidates to control CoV outbreaks with rapid/easy manufacturing, high potency, and safety. Optimal therapeutic cocktails comprising different TNAs or TNAs with other antiviral agents could act on multiple targets simultaneously, thereby enhancing antiviral effects and reducing risk of drug resistance. Lipid-ASO (LASO) nanomicelles enable cellular self-uptake and can be conjugated with antiviral molecules, providing promising anti-CoV combinational therapeutics that can be delivered directly to the lungs by aerosol. Advancement in chemical modifications and delivery vehicles remarkably enhance stability and pharmacokinetic profile of TNAs, facilitating clinical application of numerous TNAs; however, more studies on optimal chemical manufacturing and delivery methods improving safety and efficiency for TNAs are needed.